Diagnostic challenge of mycosis fungoides: a case report of progression in a 46-year-old Filipino woman - Guieb, Michaela Gabrielle G.; Dagala, Ron Michael P.; Gulmatico-Flores, Zharlah (Annals of Lymphoma, 2026)
Background: Cutaneous T-cell lymphomas (CTCL) are a group of rare, heterogeneous skin disorders characterized by malignant T-cell proliferation. The pathogenesis involves complex genetic and environmental interactions. Diagnosis is challenging due to CTCL’s resemblance to benign conditions like eczema or psoriasis and its indolent progression over decades. Mycosis fungoides (MF) and Sézary syndrome (SS) account for the majority of cases, with increasing incidence among older adults, men, and African Americans. Furthermore, MF is more commonly observed in males, making studies specifically focused on middle-aged Filipino women rare. This case enriches and diversifies the clinical literature in this area.Case Description: This is a 46-year-old Filipino female with a one-year history of recurrent, pruritic erythematous patches and plaques initially diagnosed as contact dermatitis on biopsy. Hence, patch testing was done and resulted in negative responses for the 30 haptens tested. Initial treatments with topical clobetasol propionate 0.05% lotion provided temporary relief of pruritus but with persistent lesions. Some patches evolved into plaques, which revealed parapsoriasis on biopsy. However, the appearance of nodules prompted multiple biopsies which later confirmed MF, stage IIB (T3N1aM0B0), supported by histopathology and immunohistochemistry (CD3+, CD20+, CD30−). Imaging revealed hypermetabolic lymph nodes and skin lesions without systemic malignancy. Despite skin-directed therapies, including narrowband ultraviolet B phototherapy, topical clobetasol propionate 0.05% lotion, and tretinoin 0.05% cream, disease progression necessitated systemic methotrexate 10 mg weekly as an immunosuppressive and cytotoxic agent, followed by referral for targeted therapies such as monoclonal antibodies and biologics aimed at controlling T-cell proliferation. Unfortunately, the patient was lost to follow-up and succumbed to her illness.Conclusions: This case underscores that MF can mimic common skin disorders, often remaining undiagnosed for years due to its slow course. Persistent or worsening lesions despite standard therapy should prompt further evaluation by a dermatologist to exclude malignancy. Accurate diagnosis, staging, and risk assessment require a multidisciplinary approach. While systemic therapies may achieve high response rates, these are often temporary and associated with significant side effects, highlighting the need for careful, individualized treatment planning.